Business Strategy to Increase Revenue at Service Division PT. XYZ Elevator - Ferry, Yhonna; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2015)
Abstract.PT. XYZ, registered since 1964 as an agent in Indonesia Elevator XYZ. Since the installation of the first elevators in Indonesia in 1963, it can be said that the age of the lift is installed already exceeded 15 years. Of the total portfolio of 2362 units bound by contract maintenance services, over 700 units have been outstanding for more than 15 years. As the main component of which is essential in a building, maintenance service contracts awarded must provide assurance that the unit is well maintained.Just like any mechanical system, engine life will have an impact on the performance and safety of the elevator system. With this situation, interface product requested to be applies in renewal system installed elevator. Under these conditions the final task is to determine the right business strategy to be applied to increase revenue in service division PT. XYZ.In determining the business strategy, methodology used in this thesis is a qualitative internal and external analyze factors. Marketing strategy analyzing to determines the right strategy for the formulation of PT. XYZ. The technique used in this method is to gather information, perform analysis, and conclusions.Conclusion of this final project to formulated Modernization sales product package, focusing on update technology as the value preposition. This package will be offer to the existing customer as the priority but not limited, for others brand meet with specification also can be apply. The right time to be launching should be assured to get high benefit to meet the final target.Keywords: Elevator,Maintenance contract service, Increase revenue, Elevator life time, Modernization elevator, Business Strategy, Business Model CanvasÂ Â